Diffusion of methylrosaniline chloride from emulsified ointment bases - Abundo, Lilia (Cajator) 1935-
The literature on the subject of release of medication from ointment bases is vast but vague. Much of the information is descriptive. A method was developed, patterned after that devised by Enver Izgu and C.O. Lee (1), which consisted in placing the ointment in tared plastic disc, the excesses leveled off, and the weights determined. The disc were inverted on pre-cut, pre-weighed filter paper. Contact time was set at 8, 16, and 24 hours. At the end of the required period, the disc were removed, the remaining ointment on the filter paper were carefully scraped off and the diffusion zone cut out for subsequent extraction. The amount that was diffused over 8, 16, and 24 hours were then determined by extracting the Methylrosaniline Chloride with alcohol and assaying in a Beckman model DU Spectrophotometer at 305 mu. Since experiments in quadruplicate were prepared for the diffusion at 8, 16, and 24 hours contacts, the spectrophotometric assay devised, provides a rapid quantitative estimate of each individual trial when compared with the official assay which is a long and tedious process. The technique is simple and the method inexpensive. Two types of preparations were employed in these studies: an oil-in-water and a water-in-oil emulsified base. Methylrosaniline Chloride was added as a "typical" water-soluble active ingredient. The latter also performed the role of a visible criterion of diffusion. In oil-in-water as well as in water-in-oil bases, it was observed that the rate of diffusion during the first eight hours increased with lanolin concentration. For periods longer than eight hours, the diffusion rates generally decreased. In oil-in-water bases, the rate seemed to approach a constant. In water-in-oil bases, the rate of diffusion for periods longer than eight hours appeared as an inverse function of the lanolin concentration. An assessment of the total amount of Methylrosaniline Chloride diffused over 8, 16, and 24 hours, demonstrates the greater efficiency of the water-in-oil base in releasing the drug from the vehicle.
Available to the general public.
Thesis (Master of Science)--University of the Philippines, November 1965.
Keywords: Excipients; Diffusion; Methylrosaniline chloride; Chemistry, Medical and pharmaceutical